2023
DOI: 10.31234/osf.io/2dcvf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“I’m so dumb and worthless right now”: Factors associated with heightened momentary self-criticism in daily life

Abstract: The trait of self-criticism is a transdiagnostic risk factor for psychopathology. Although self-criticism is certainly an individual difference, whereby people higher in self-criticism are more vulnerable to psychopathology compared to people low in self-criticism, self-criticism is also something people can do in moments of time. The current study describes the development of a brief index of momentary self-criticism using ecological momentary assessment, with the aim of exploring factors associated with heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…For manipulation checks, participants were then asked questions addressing their imagined willpower, distress tolerance and coping self‐efficacy (same as Study 1), and both self‐criticism and self‐compassion. These included the three self‐compassion items from the state self‐criticism scale (Neff et al., 2020), and five items from a brief index of momentary self‐criticism (e.g., “I'm mentally beating myself up right now”) originally developed for experience sampling (Veilleux et al., 2023), with items given on a scale from 0 ( not at all ) to 6 ( extremely ). Both the self‐compassion ( α = 0.72) and self‐criticism items ( α = 0.93) had good reliability.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For manipulation checks, participants were then asked questions addressing their imagined willpower, distress tolerance and coping self‐efficacy (same as Study 1), and both self‐criticism and self‐compassion. These included the three self‐compassion items from the state self‐criticism scale (Neff et al., 2020), and five items from a brief index of momentary self‐criticism (e.g., “I'm mentally beating myself up right now”) originally developed for experience sampling (Veilleux et al., 2023), with items given on a scale from 0 ( not at all ) to 6 ( extremely ). Both the self‐compassion ( α = 0.72) and self‐criticism items ( α = 0.93) had good reliability.…”
Section: Methodsmentioning
confidence: 99%
“…Thus far, associations between self‐criticism and suicidality have been primarily examined at a trait level. However, even people who tend toward harsh and judgmental views of the self are not self‐critical in all situations, and self‐criticism can vary over time (Veilleux et al., 2023; Zuroff et al., 2016). Recent work demonstrated that state self‐criticism and state self‐punishment cognitions were associated with concurrent urges to engage in non‐suicidal self‐injury (Burke, Fox, Kautz, Rodriguez‐Seijas, et al., 2021; Forkmann et al., 2018).…”
Section: Self‐criticismmentioning
confidence: 99%
See 1 more Smart Citation